Perempuan dalam Konflik Aceh - HASNI, KHAIRUL (Politeia: Jurnal Ilmu Politik, 2012)
This is a study about women in Aceh during and after conflict. Serius human right violation against women, including rape and another forms of sexual abuse, have been reported in Indo-nesiaâs Aceh during the last decades. The military repression continued for a decade until the collapse of Suhartoâs authoritarian goverment in May 1998. Democatization started since then, but it did not affect the situation in Aceh as the military continued the internal war which was endorsed by the post-Suharto civilian president. The oppotunity for peace finally arrived in the end of 2004 when Aceh was hit by tsunami. This research treis to understand how the condition of women changed before and after the peace-settlement. Many literatures on Acehâs conflict tend to highlight the âsuccess storyâ of its post-conflict recovery which has been suported by various approach. However, this research found that women are still marginalized in various recontruction initiative largely due to the very lack of gender equality perspective in these ef-fort. Therefore, Acehnes women face new challenge in the age of âpeaceâ.Keywords: Conflict War, Violent, Human right.